Combinação de reações organocatalíticas e multicomponentes para a síntese de sistemas heterocíclicos e moleculas híbridas - Pérez, Radell Echemendía (Universidade Federal de São Carlos, 2019)
Small enantiomerically pure or enriched organic molecules are key starting materials in organic synthesis. Chiral building blocks are in high demand in the overall synthesis of complex natural products and in the discovery and development of drugs as well as in the production of advanced pesticides, fragrances and materials. In this sense, organocatalytic methodologies have emerged as a third pillar of asymmetric catalysis and have a prominent position in the development of more sustainable methods. Similarly, multicomponent reactions (MCRs) present themselves as a powerful tool for the synthesis of bioactive heterocyclic compounds and analogues of natural products. Chiral aldehydes are key components in stereocontrolled MCRs, methods for the asymmetric functionalization of carbonyl compounds are relevant for the development of novel multicomponent stereoselective approaches. In recent years, our group and the Banfi group have been exploring the potential of organocatalysis to generate compounds enantiomerically enriched with the synthetic power of MCRs in the diversification of these chiral compounds. In this work we describe a highly stereoselective methodology for the synthesis of natural product hybrids from an organocatalytic tandem procedure, followed by a multicomponent reaction. Effectively, the procedure comprises an organocatalysed conjugate addition of active methylene compounds (1,3-dicarbonyls and α ester or cyanoketones) to α,β-unsaturated aldehydes to form asymmetric hemiacetals containing orthogonal functional groups. Next, an isocyanate based intramolecular multicomponent reaction is implemented. Through the use of this approach it was possible to synthesize hybrids of natural products, including up to four different molecular fragments, such as hydroquinoline, tetrahydropyridine, peptides, lipid and glycoside units
Merging organocatalytic and multicomponent reactions for the synthesis of heterocyclic scaffolds and hybrid molecules
Keywords: Sintese orgánica; Organic compounds - Synthesis; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::SINTESE ORGANICA